2018
DOI: 10.1590/1807-3107bor-2018.vol32.0023
|View full text |Cite
|
Sign up to set email alerts
|

Medication-related osteonecrosis of the jaw, osteoradionecrosis, and osteomyelitis: A comparative histopathological study

Abstract: It is largely known that some oral diseases can be diagnosed based upon their clinical manifestation combined with the patient's medical history and generally not depending on examination. This is the case of some bone diseases such as osteoradionecrosis of the jaw (ORNJ), osteomyelitis of the jaw (OMJ), and medication-related osteonecrosis of the jaw (MRONJ). The present study aimed to analyze the histopathological features of these specific bone diseases in order to evaluate similarities and differences. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
4
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 15 publications
5
26
4
13
Order By: Relevance
“…Additionally, an increased quantity of empty lacunae was found in the ZA E site compared to Control E site (Fig 4). Empty lacunae is one diagnostic factor for osteonecrosis [12, 13] and is consistent with other findings in mice MRONJ lesions [23]. Interestingly, the greatest amount of empty lacunae was found at E sites, but not in the NE sites in ZA-treated mice (S2 Fig).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, an increased quantity of empty lacunae was found in the ZA E site compared to Control E site (Fig 4). Empty lacunae is one diagnostic factor for osteonecrosis [12, 13] and is consistent with other findings in mice MRONJ lesions [23]. Interestingly, the greatest amount of empty lacunae was found at E sites, but not in the NE sites in ZA-treated mice (S2 Fig).…”
Section: Discussionsupporting
confidence: 88%
“…In our histopathological analysis, 100% of our ZA treated mice presented a delayed bone healing and MRONJ lesions histological characteristics (Figs 4 and 5). These compare with other findings in mice [23, 39], rats [61, 62, 64] and humans [12, 13], including intense leukocyte infiltration, areas of non-vital bone and discrete bone sequestrum.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study also showed similar results where the inflamed connective tissue was exposed without the epithelial coverage, thin trabeculae was lined with rare multinuclear osteoclasts, and marrow spaces infiltrated with the inflammatory cells detected in the alveolar bones in our animal MRONJ‐like lesions. However, the histological feature of MRONJ may overlap with osteomyelitis . MRONJ may be considered as an adverse drug reaction consisting of progressive bone destruction in the maxillofacial region under current or previous treatment with antiresorptive and antiangiogenic medications, exposed bone, and no history of radiation therapy or obvious metastatic disease to the jaws .…”
Section: Discussionmentioning
confidence: 99%